Thermal treatment effect on dynamics of luminescent states in oxyfluoride glass-ceramics doped with Pr3+ and Tb3+ - Dominiak-Dzik, Grażyna; Klimesz, Barbara; Ryba-Romanowski, Witold (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The 50GeO2–(50–x–y)PbO–yPbF2–xLnF3 glass single doped with Pr3+ and Tb3+ ions was studied. The composition of the material was modified by varying the content of both PbF2 (y = 5, 10, 15 mol%) and LnF3 (x = 0.2 and 2 mol%). The differential thermal analysis (DTA) of as-melted samples was used to determine thermal characteristics. Optical techniques and kinetics measurements were used to monitor the effect of thermal treatment on spectroscopic properties and dynamics of luminescent states of optically-active ions in amorphous and two-phase systems. It was found that non-exponential decays of praseodymium luminescence in as-melted material become exponential or nearly exponential with corresponding longer lifetimes in thermally-treated samples. This effect was not so strong in the Tb3+-doped glass. The influence of the PbF2 content on luminescence dynamics was studied for samples doped with 2 mol% of Pr3+. It was observed that the increase of PbF2 content leads to lengthening of luminescence lifetime, e.g., the 1D2 lifetime increases from 4.1 to 45 μs in 5 and 15 mol% of PbF2 as-melted samples, respectively.
Optica Applicata, Vol. 40, 2010, nr 2, s. 375-382
Keywords: optyka; oxyfluoride glasses; differential thermal analysis (DTA); thermal treatment; optical properties; luminescence dynamics; lifetimes